(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The investigative work was aimed at knowing the perceptions of the fourth grade teachers of the official educational institution Pablo Correa León, Valle Esther headquarters in the city of Cúcuta, about the educational processes with Venezuelan students, stating the successes in the processes and the barriers. educational. It was known that teachers perceive in the educational processes with Venezuelan students, the presence of low academic performance, little responsibility and commitment in the training component. Additionally, they highlight the manifestation of talents in the area of ​​the arts, highlighting the cultural knowledge, worldviews and skills of the population group. Likewise, they observe educational barriers, associated with the difficulties presented in responsibly assuming the educational process; Although, they perceive that students show successes regarding intentions to continue with the learning processes.